Use of dehydrated distillery grains with solubles in diets for fattening rabbits - V?zquez, Ysnagmy; Bernal, H.; Valdivi?, Manuel; Guti?rrez, E.; Castellanos, L. M.; Hern?ndez, C. A.; Ju?rez, A.; Cerrillo, Mar?a A. (Cuban Journal of Agricultural Science, 2013)
In order to assess the inclusion of 0, 10, 20 and 30 % of dehydrated distillery grains with solubles (DDGS) in diets for fattening rabbits, 56 animals (Black Aztec x Chinchilla) of 40 d of age were used. The productive performance from weight gains, feed conversion, viability, feed intake, mean daily gain, carcass yield, meat, bones and fat of the rabbits was determined, as well as the yield of edible viscera. The viability was of 100 % in all the treatments. The rabbits consuming the diet with 10 % of DDGS consumed less feeds (91.8 g/rabbit), and determined better feeding conversion index (4.21). Those animals receiving the diet with 20 % of DDGS obtained higher weight (2051 g/ rabbit). The carcass yield did not differ significantly between treatments. The rabbits with 30 % of DDGS in the diet achieved higher yield in edible viscera (8.8 %). The neck yield was higher in those with 20 % of DDGS in the diet (4.9 %). There were no significant differences for meat and fat yield in the carcass. The inclusion of up to 20 % of DDGS in feedstuff for fattening rabbits is possible without altering the carcass yield. Key words: DDGS, fattening rabbits, productive performance, carcass yield.